Speech outcomes of myanmar children with cleft lip and palate: Primary study - B. Prathanee (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019. Background: Multidisciplinary team approaches for cleft lip and palate (CLP), especially speech services are limited in Myanmar. Standard testing and speech services need to be established. Objective: Our aim was to compare speech outcomes among Myanmarese children with CLP vs. normal children. Materials and Methods: A descriptive 2-group study was conducted at Tachileik, Myanmar. Participants were recruited, including 10 Myanmarese children with CLP, who had undergone cheiloplasty and palatoplasty, and 10 normal children. The children were all students between 6 and 14 years of age in Grades 1 to 7. The standard Myanmar Articulation, Resonation, Nasal Emission and Nasal Turbulence Test and Articulation Screening Test were used for eliciting speech outcomes. Descriptive statistics were used for the demographic data, the Wilcoxon Sign Rank Test to determine articulation difference between children with and without CLP, and correlation to investigate the relationship between standard and screening tests. Results: Ninety percent of children with CLP had functional articulation disorders. Phonological disorders, particularly voiceless for voice, was the most common type in children with CLP while 3 of the normal children had only 1 error sound. Children with CLP also had significantly more misarticulation sounds than typical children on the word, sentence, and connected speech level based on screening tests (median difference: MD = 5.5, 95% confidence interval (CI) = 4, 8; MD = 5, 95% CI = 5, 6; MD = 5.5, 95% CI = 4, 8 respectively). The Standard Burmese Articulation, Resonation, Nasal Emission, and Nasal Turbulence Test had a high correlation to the Screening Test at the word level (r = 0.81, 95% CI = 0.36, 0.95). Conclusion: Children with CLP in Myanmar are at high risk of articulation errors and need critical speech services.